"Parenteral" Diarrhea Associated With Pediatric Urinary Tract Infections: A Retrospective Chart Review. Issue 8 (12th August 2022) - Mellick, Larry B.; Murray, Caleb; Kalra, Sarathi
Abstract : Objectives: The association of noninfectious diarrhea with extraintestinal infections such as otitis media, pneumonia, or febrile urinary tract infections (UTIs) is commonly known as parenteral diarrhea. Although this association has been described for over a century and parenteral diarrhea is mentioned in current reference literature, available evidence for this association seems to be limited. The primary research question was to determine if there is an association between UTIs and reports of diarrhea. Methods: A retrospective chart review was performed using the medical records from October 1, 2017, to March 29, 2019 at our tertiary pediatric medical center. We searched for all cases of afebrile and febrile UTIs evaluated in the pediatric emergency department or admitted directly to the hospital for treatment. All children younger than 5 years were eligible for inclusion. Exclusion criteria included children with recent urological procedures, known urinary tract disease, immune suppression, sepsis, or known gastrointestinal diseases. The medical records of each of the pediatric patients with culture-positive UTIs were reviewed for reports of concurrent diarrhea or diarrhea-like illness. In addition, using a comparative quantitative design, we performed a retrospective chart review of all children younger than 5 years with 1 of 2 noninfectious chief complaints, head trauma, and extremity fractures, presenting during the same period to assess the background rate of reported diarrhea. This research project received the approval of the University of South Alabama's Institutional Review Board. Results: A total of 236 children with a culture-positive UTI presented to our pediatric medical center from October 1, 2017 to March 29, 2019. Reports of diarrhea were documented in the medical record for 44 of the 236 UTIs (18.6%). Escherichia coli was the predominant infectious agent in 32 of the 44 children (72.7%) with culture-positive UTIs and diarrhea. Of the 368 comparison group patients who visited the pediatric emergency department for a noninfectious complaint, diarrhea was reported in 2 patients (0.01%). Conclusions: Our retrospective review of pediatric patients younger than 5 years with culture-proven UTIs found an association of reported diarrhea. It is our opinion based on our single-center retrospective chart review that the current available evidence suggests an association between UTIs and extraintestinal diarrhea. Future prospective studies are recommended to confirm this association.